Competition between s-wave order and d-wave order in holographic superconductors - Li, Li-Fang; Cai, Rong-Gen; Li, Li; Wang, Yong-Qiang (2014)
We study competition between s-wave order and d-wave order through two holographic superconductor models. We find that once the coexisting phase appears, it is always thermodynamically favored, and that the coexistence phase is narrow and one condensate tends to kill the other. The phase diagram is constructed for each model in terms of temperature and the ratio of charges of two orders. We further compare the behaviors of some thermodynamic quantities, and discuss the different aspects and identical ones between two models.